Insider Trading and Voluntary Disclosures - CHENG, QIANG; LO, KIN (Journal of Accounting Research, 2006)
ABSTRACT We hypothesize that insiders strategically choose disclosure policies and the timing of their equity trades to maximize trading profits, subject to the litigation costs associated with disclosure and insider trading. Accounting for endogeneity between disclosures and trading, we find that when managers plan to purchase shares, they increase the number of bad news forecasts to reduce the purchase price. In addition, this relation is stronger for trades initiated by chief executive officers than for those initiated by other executives. Confirming this strategic behavior, we find that managers successfully time their trades around bad news forecasts, buying fewer shares beforehand and more afterwards. We do not find that managers adjust their forecasting activity when they are selling shares, consistent with higher litigation concerns associated with insider sales. Overall, our evidence suggests that insiders do exploit voluntary disclosure opportunities for personal gain, but only selectively, when litigation risk is sufficiently low.